Hubungan antara Indeks Massa Tubuh dan Lingkar Pinggang dengan Kejadian Hipertensi Sistolik Terisolasi pada Lansia - Yasinta Saraswati Hakim; Setyoko Setyoko; Yanurita Tursinawati (Fakultas Kedokteran Universitas Trisakti, 2022)
BackgroundGlobally, it is estimated that 15% of the elderly had isolated systolic hypertension (ISH). ISH in the elderly may occur because of the aging process or other risk factors, such as obesity. Obesity is divided into total obesity which is measured by body mass index (BMI), and abdominal obesity which is measured by waist circumference (WC). The difference in these measurement parameters made this study aim to determine the relationship between BMI and WC with the incidence of ISH in the elderly. MethodsThe study was an analytical observational cross-sectional method and used a consecutive sampling technique with the samples aged ≥ 60 years old that had ISH. The research measured blood pressure, weight, height, and waist circumference. The data was analyzed by Rank Spearman test for the relationship between BMI with the incidence of ISH and Chi-Square test for the relationship between waist circumference with the incidence of ISH, with α values for both tests being 0,05. ResultsThe samples in this study were 110 elderlies with the most criteria being young elderlies (60%), female gender (67,3%), work as farm worker/farmer (41,8%), ISH grade I (66,4%), obesity (36,4%), and abdominal obesity (54,5%). There was no relationship between BMI with the incidence of ISH in the elderly (p= 0,827) but had a relationship between waist circumference with the incidence of ISH in the elderly (p= 0,001). ConclusionsBMI as an indicator of total obesity is not associated with the incidence of ISH in the elderly, but waist circumference as an indicator of abdominal obesity shows a relationship with the incidence of ISH in the elderly.